دور المعايير المحاسبية الدولية في الرفع من كفاءة السوق المالي الجزائري - قريرة رشيد; دادن عبد الغني (جامعة الوادي University Of Eloued, 2024)
تهدف هذه الدراسة إلى التعرف على واقع تطبيق المعايير المحاسبية الدولية التي لها علاقة بالسوق المالي الجزائري سوى بطريقة مباشرة أو غير مباشرة، كما تهدف إلى التعرف على كفاءة أو عدم كفاءة السوق المالي الجزائري، بينما الهدف الرئيسي من هذه الدراسة هو التعرف على العلاقة بين المعايير المحاسبية الدولية وكفاءة السوق المالي الجزائري، وافترضنا وجود علاقة طردية بين المعايير المحاسبية الدولية وكفاءة للسوق المالي الجزائري، وتم استخدام الاستبيان كأداة لجمع البيانات، معتمدين على مجموعة من الأدوات الإحصائية كالمتوسط الحسابي والانحراف المعياري ومعامل الارتباط والشبكة العصبية، وتم التوصل إلى أن مستوى تطبيق المعايير المحاسبية الدولية عالي، كما توصلنا إلى أن السوق المالي الجزائري كفء، وفي المقابل توصلنا إلى وجود علاقة طردية بين المعايير المحاسبية الدولية وكفاءة السوق المالي الجزائري. This study aims to identify the reality of the application of international accounting standards that are related to the Algerian financial market only directly or indirectly, and also aims to identify the efficiency or inefficiency of the Algerian financial market, while the main objective of this study is to identify the relationship between accounting standards international and the efficiency of the Algerian financial market, We assumed the existence of a direct relationship between international accounting standards and the efficiency of the Algerian financial market, and the questionnaire was used as a tool for data collection, relying on a set of statistical tools such as the arithmetic mean, standard deviation, correlation coefficient and the neural network, and it was concluded that the level of application of international accounting standards is high, and we also concluded that The Algerian financial market is efficient, and on the other hand, we found a positive relationship between international accounting standards and the efficiency of the Algerian financial market.
The impact of international accounting standards in raising the efficiency of the Algerian financial market
Keywords: معايير محاسبية دولية; سوق مالي; كفاءة سوق مالي; international accounting standards; financial market; financial market efficiency